2008
DOI: 10.1007/s12031-008-9035-0
|View full text |Cite
|
Sign up to set email alerts
|

Features and Functions of Oligodendrocytes and Myelin Proteins of Lower Vertebrate Species

Abstract: The myelin-forming cells in the central nervous system (CNS) of lower vertebrate species, in particular those of fish, profoundly differ from their mammalian counterparts in their biochemical phenotype in that they express Po-like glycoproteins as major myelin protein constituents instead of proteolipid protein, while in their overall cellular structure and their cell lineage relationships, they closely resemble mammalian oligodendrocytes. While molecular biology in the past has allowed to appropriately classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
1
20
0
2
Order By: Relevance
“…Moreover, the fact that NgR signaling upon ZF-Nogo66 binding promotes growth predicts that additional ligands of NgR such as MAG, OMGP, and further myelin proteins negatively affecting axon growth in mammals (Yiu and He, 2006), probably have no or only weak inhibitory influence on axon growth in fish, or are simply absent (such as the NogoA-specific domain). In addition, fish possess their own myelin components such as the proteins 36k and IP-1 and IP-2 (Jeserich et al, 2008) that are absent from mammals. Furthermore, no glial scar-associated growth inhibition exists in goldfish (Hirsch et al, 1995) and glial cell-derived soluble factors actually support axon regeneration (Schwalb et al, 1996).…”
Section: Nogo-66 In the Path Of Regenerating Axonsmentioning
confidence: 99%
“…Moreover, the fact that NgR signaling upon ZF-Nogo66 binding promotes growth predicts that additional ligands of NgR such as MAG, OMGP, and further myelin proteins negatively affecting axon growth in mammals (Yiu and He, 2006), probably have no or only weak inhibitory influence on axon growth in fish, or are simply absent (such as the NogoA-specific domain). In addition, fish possess their own myelin components such as the proteins 36k and IP-1 and IP-2 (Jeserich et al, 2008) that are absent from mammals. Furthermore, no glial scar-associated growth inhibition exists in goldfish (Hirsch et al, 1995) and glial cell-derived soluble factors actually support axon regeneration (Schwalb et al, 1996).…”
Section: Nogo-66 In the Path Of Regenerating Axonsmentioning
confidence: 99%
“…This suggests an evolutionary neuroprotective change in myelin chemistry between aquatic and terrestrial vertebrates, which is supported by the degenerative phenotype observed in transgenic mice that express P 0 instead of Plp in their CNS (Yin et al, 2006). Although there is sequence conservation between zebrafish and mammalian P 0 (Schweitzer et al, 2003), the zebrafish p 0 gene shows greater promoter region sequence conservation with the mammalian Plp gene rather than mammalian P 0 (Jeserich et al, 2008;Jeserich et al, 1997). In keeping with this, a zebrafish transgenic line, which expresses enhanced green fluorescent protein (EGFP) under the regulation of a mouse Plp promoter, exhibits strong EGFP expression in oligodendrocytes and their precursors, although it is not clear whether this promoter regulates zebrafish dm20 or p 0 genes (Yoshida and Macklin, 2005).…”
Section: Zebrafish and Mammalian Myelin: A Comparisonmentioning
confidence: 96%
“…The major biochemical difference between zebrafish and mammalian myelin is the presence of protein zero (P 0 ) as a major CNS myelin protein in zebrafish, rather than PLP in mammals (Table 1) (Jeserich et al, 2008;Waehneldt et al, 1986). This suggests an evolutionary neuroprotective change in myelin chemistry between aquatic and terrestrial vertebrates, which is supported by the degenerative phenotype observed in transgenic mice that express P 0 instead of Plp in their CNS (Yin et al, 2006).…”
Section: Zebrafish and Mammalian Myelin: A Comparisonmentioning
confidence: 99%
See 2 more Smart Citations